Thermische und säurekatalysierte Umlagerung von N-Allyl-anilin und Derivaten - S. Jolidon; H.-J. Hansen (CHIMIA)
The thermal (t-amyl alcohol, 310 to 340°) and acid catalyzed (2N H2SO4, 145-170°) rearrangement of N-allyl-aniline (1), N-allyl-N-methyl-aniline (2) and (E)- and (Z)-N-but-2'-enyl-aniline [(E)- and (Z)-3] was investigated. In contrast to earlier reports, 1 rearranges thermally to yield 2-allyl-aniline (4), but an appreciable amount of aniline (30-40%), resulting from homolysis, is also formed (scheme 1). The kinetic secondary H/D isotope effect (kH/kD) for the rearrangement of 1 and β,β,γ-d3-1 is almost negligible (0,98 ±0,09; 340°), but the deuterium in 4 is, in accordance with a [3,3]-sigmatropic process, exclusively located at C(α) and C(β). The anilines 2 and (E)- and (Z)-3 show, on heating, much higher portions of splitting (~ 60 %) and side reactions (~ 20-30 %). The amounts of the rearranged anilines 5 and 6 (with inverted allyl chain) are in the order of 10-20% (scheme 2). On the other hand, all anilines undergo clean [3,3]-sigmatropic transformations in 2N H2SO4 to give the corresponding 2-allylated anilines 4, 5 and 6, respectively (scheme 3). Almost no decomposition (< 2%) into aniline or N-methyl-aniline is observed. The acceleration factors (kH+/kΔ) at 310° are in the order of 106 (see table 1).